2001
DOI: 10.1097/00006676-200107000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility to Cerulein-Induced Pancreatitis in Inducible Nitric Oxide Synthase-Deficient Mice

Abstract: Production of nitric oxide (NO) by inducible nitric oxide synthase (iNOS) has been proposed as a pathogenic factor in acute pancreatitis, but its role has still not been fully examined. The present study explored the role of iNOS in cerulein-induced acute pancreatitis using iNOS-deficient mice. Twelve- to 14-week-old male mice (C57B1/6 and iNOS-deficient) were administered cerulein by intraperitoneal (i.p.) injection at hourly intervals for 7 hours and killed 24 hours later after the first dose. Pancreatic wet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 31 publications
0
21
0
Order By: Relevance
“…Cuzzocrea et al [21] reported that iNOS-deficient mice showed resistance to acute pancreatitis induced by cerulein, suggesting a deleterious role of iNOS/NO in the pathogenesis. By contrast, Qui et al [22] reported that iNOS-deficient mice were more susceptible to cerulein-induced pancreatitis. Furthermore, using eNOS-deficient mice, DiMagno et al [8] showed a protective influence of eNOS/NO on ceruleininduced acute pancreatitis.…”
Section: Discussionmentioning
confidence: 91%
“…Cuzzocrea et al [21] reported that iNOS-deficient mice showed resistance to acute pancreatitis induced by cerulein, suggesting a deleterious role of iNOS/NO in the pathogenesis. By contrast, Qui et al [22] reported that iNOS-deficient mice were more susceptible to cerulein-induced pancreatitis. Furthermore, using eNOS-deficient mice, DiMagno et al [8] showed a protective influence of eNOS/NO on ceruleininduced acute pancreatitis.…”
Section: Discussionmentioning
confidence: 91%
“…Studies have shown that iNOS response varies between pancreatitis models and reported that, in necrotizing pancreatitis, various soluble factors activate the macrophage/monocyte system and cause increased NO production by iNOS [23] . Two groups reported on the conflicting effects of iNOS gene deletion on the late inflammatory phase of cerulein-induced AP in mice; iNOS gene deletion was protective in one study [13] and injurious in the other [24] . Our study shows that iNOS expression is substantially upregulated in the pancreas and acinar cells in response to supramaximal cerulein.…”
Section: Discussionmentioning
confidence: 99%
“…These differing results could result from different models of pancreatitis, or may be attributable to different drug regimens that achieve partial or complete inhibition of NOS. Recently, special iNOS gene deletion "knockout" mice have been used to characterize the impact of NO form iNOS during acute pancreatitis (8,28). However, these animal studies also have yielded ambiguous evidence in support of the role of NO in pancreatitis.…”
Section: Discussionmentioning
confidence: 99%